The prevention and treatment of breast cancer- related lymphedema: A review - McEvoy, Maureen P.; Gomberawalla, Ameer; Smith, Mark; Boccardo, Francesco M.; Holmes, Dennis; Djohan, Risal; Thiruchelvam, Paul; Klimberg, Suzanne; Dietz, Jill; Feldman, Sheldon (Frontiers in Oncology, 2022)
Importance: Breast cancer related lymphedema (BCRL) affects about 3 to 5 million patients, about 20,000 per year in the United States. As breast cancer mortality is declining due to improved diagnostics and treatments, the long-term effects of treatment, such as BCRL need to be addressed. Observations: We performed a comprehensive, but not a systematic review of the literature. This was inclusive of recent randomized controlled trials, meta-analyses, and reviews evaluating the prevention and treatment of BCRL. Twenty-five randomized clinical trials, 13 systemic reviews and meta-analyses and 87 observational studies were included. Prevention of BCRL is essential before chronic, irreversible lymphedema occurs. Early detection can be done with various non-invasive methods in clinic and should be monitored at regular intervals for the first two years. Reduction of risk factors, such as de-escalating axillary surgery, performing smarter axillary surgery by mapping out the upper extremity lymphatics, and safely minimizing radiation all help in prevention. Treatment can be nonsurgical involving comprehensive decompressive therapy. Surgical treatment of lymphedema can focus on ablative or physiologic procedures. Conclusions and Relevance: Prevention and treatment of BCRL involves a multidisciplinary team. Early detection, before clinically apparent, is crucial to prevent irreversible lymphedema. Awareness of risk factors, and appropriate practice adjustments to reduce the risk aides in a decrease in progression of lymphedema. The treatment can be costly, time consuming, and not always effective, and therefore the overall goal should be prevention.